The Influence of Entrepreneurship Course Toward The Student's Entrepreneurship Interest - Fenny Arfany (Journal of Career and Entrepreneurship, 2022)
The university is considered the most appropriate place to develop entrepreneurial talent through education which is expected to be able to bring up innovative and creative entrepreneurs to create jobs in the midst of the endless unemployment problem. This research aims to know the influence of entrepreneurship course toward the student’s entrepreneurship interest. This type of research is an explanatory research which is included in the quantitative method with a questionnaire for data collection. The sampling technique used was accidental sampling technique. Data analysis used was using Path Analysis and used the SmartPLS 3.0 program. These results of this study indicate that entrepreneurship course has a significant positive effect on the student’s entrepreneurship interest.